Pertanggungjawaban Pidana Pelaku Kejahatan Cyber Terrorism Dalam Undang-Undang Nasional - Gefbi Nopitasari; Riska Andi Fitriono (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
The creation of the internet, which is used to make human life easier, has become a new problem because it has given rise to cyber crime in cyberspace. One of the cyber crimes currently developing is cyber terrorism. This research examines the crime of cyber terrorism from the perspective of the perpetrator's criminal responsibility according to national laws in Indonesia. The method used in this research is a normative juridical legal research method that is perspective based on literature study. The legal materials used are primary and secondary legal materials. Data analysis techniques using deductive logical reasoning. The research results show that the term cyber terrorism crime has not been mentioned grammatically in national legislation. However, several articles in Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions contain the substance of cyber terrorism crimes, namely Article 28 paragraph (2), Article 28 paragraph (3), Article 31 and Article 33. The legal subject, namely the perpetrator in this article, is "Person" which means an individual or legal entity/corporation. All of these articles contain elements of "acts against the law" whose substance corresponds to the crime of cyber terrorism. So that a person or legal entity that commits acts in accordance with this article can be held criminally responsible. The legal sanction for this crime is imprisonment and/or a fine.